Atrocity speech law : foundation, fragmentation, fruition - Gordon, Gregory S. (New York, NY : Oxford University Press, 2017)
Prof. Gordon provides a broad analysis of the entire jurisprudential output related to speech and gross human rights violations for courts, government officials, and scholars. The book is organized into three parts. The first part covers the foundation: a brief history of atrocity speech and the modern treatment of hate speech in international human rights treaties and judgments under international criminal tribunals. The second part focuses on fragmentation: detailing the inconsistent application of the charges and previous prosecutions, including certain categories of inflammatory speech and a growing doctrinal rift between the ICTR and ICTY. The last part covers fruition: recommendations on how the law should be developed going forward, with proposals to fix the problems with individual speech offenses to coalesce into three categories of offense: incitement, speech-abetting, and instigation
Speech and atrocity : an historical sketch -- International human rights law and domestic law -- The birth of atrocity speech law : Nuremberg and the foundational statutes -- The birth of atrocity speech law : the foundational ad hoc tribunal cases and offense elements -- Problems regarding the crime of direct and public incitement to commit genocide -- Problems regarding persecution, instigation, and ordering -- The absence of criminal prohibitions regarding hate speech and war crimes -- Fixing incitement to genocide -- Fixing persecution, instigation, and ordering -- Adopting incitement to commit war crimes -- Restructuring : a unified liability theory for atrocity speech law
BIBINDX
Keywords: Hate speech -- Law and legislation; Atrocities; Hate crimes; War crimes; Genocide; International law and human rights